OPTIMIZATION THE ROLE AND FUNCTION OF THE COMMUNITY POLICE IN MAINTAINING COMMUNITY SECURITY AND ORDERLINESS IN SIDOMUKTI VILLAGE - Pabesak, Anthon Sattu; Pasolang, Yoseph; Jaya, Apriliani Kusuma (IJBLE Scientific Publications Community Inc., 2023)
The research aims to know and describe the role and function of the Community Police in maintaining security and order in the community. This research uses an empirical juridical approach. Data collection techniques are carried out by observation, interview, and documentation studies, which then the data obtained from the research are processed using qualitative analysis methods, which then the results of the analysis are described descriptively. The results showed that the role of the Community Police in maintaining security and order in Sidomukti Village, Sukamaju District, North Luwu Regency, one of which was to overcome fights by youth groups in Sidomukti Village, namely their position as law enforcement officers (Gakkum) and as the core of Kamtibmas Coach, in this case the National Police has a duty in regulatory efforts to create security and order in the community. In addition, the role of the Police in overcoming brawls at the Bone-Bone Police Station is by conducting coaching and activities that are 1) Prefentive, such as carrying out coaching, lighting, legal counseling activities and carrying out patrols in vulnerable areas, and 2) Repressive, such as implementation in the form of enforcement of soft ones, to strict actions in the form of criminal punishment.